Synergistic Antibacterial Effects of Areca Nut Seed (Areca catechu L.) and Binahong leaf (Anredera cordifolia (Ten.) Steenis) Extracts Against Propionibacterium acnes - Nuryanti, Siska; Nurung, Ayyub Harly; Saputra, Muh. Satrio Surya; Musfatir, Harvanita; Umaiyah, Ummi Putri (Journal Microbiology Science, 2024)
Areca nut (Areca catechu L.) seeds has antibacterial properties due to their alkaloid, flavonoid, tannin, saponin, and polyphenol compounds. Binahong leaves (Anredera cordifolia (Ten.) Steenis) contain flavonoids, polyphenols, saponins, and alkaloids that also act as antibacterial agents. This study aimed to assess the antibacterial activity and synergistic effects of combining extracts from areca nut and binahong leaves against Propionibacterium acnes. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of P. acnes were evaluated for the ethanol extracts of areca nut and binahong leaves. The MIC and MBC values 400 ppm and 1.600 for extract ethanol single areca nut and 50.000 ppm and 100.000 ppm for binahong leaves. The MIC and MBC values for the combination 400/12.500 ppm and 1.600/781,25 ppm for areca nut and 50,000/800 ppm and 100,000/100 ppm for binahong leaves, respectively. The synergy between the two extracts was determined using the Fractional Inhibitory Concentration Index (FICI). The FICI value of 1. P. acnes indicates an indifferent effect (1 < FICI ≤ 4).